Dysuria and Vaginal Pain, Unusual Manifestations of B-acute Lymphoblastic Lymphoma - Ananya Datta Mitra; Anupam Mitra; Jong H Chung; Elham Vali Betts (Clinical Pathology, 2024)
Urinary symptoms are one of the most common reasons for emergency visits in females of pediatric age group and can be associated with various conditions like infections (most common), sexual trauma and rarely neoplastic processes. Here, we report a case of a 7-year-old female who presented in the emergency multiple times with the complaints of urinary symptoms and vaginal pain and was empirically treated with antibiotics and antifungals without symptomatic improvement. Her blood tests, physical examination during this time remained unrevealing. She was then transferred to our institution on her third emergency visit for further evaluation. On imaging studies, she was noted to have expansile lesions on her vertebral body at the L4 and T6 levels with compressive myelopathy with multiple bone and soft tissue lesions throughout her lower extremities. Patient developed saddle anesthesia requiring emergent decompression and biopsy of the epidural mass with the final pathology coming back as B-lymphoblastic leukemia/lymphoma. B-ALL/B-LBL is the most common pediatric hematologic malignancy and usually presents with fever, hepatosplenomegaly, lymphadenopathy, bone pain and bleeding. Occasionally, atypical presentations like bone and joint pain, osteoporosis, palpable paravertebral mass have been described. However, this is the first case report to describe a very unusual and unfamiliar presentation of this disease causing significant diagnostic difficulty resulting in delayed treatment. This case report can aid as a reminder that unusual pain or any nonspecific manifestations in pediatric patients, refractory to common treatment should be investigated with extreme diligence not to miss this neoplastic process.